The emotional needs of young children and their families : using psychoanalytic ideas in the community - Trowell, Judith; Bower, Marion, 1949- (Routledge, 1995)
Describes the ways psychoanalytic ideas can be adapted and used in a wide variety of community settings to help children who are emotionally disturbed or who have been physically or sexually abused.